A Price Worth Paying: Hodgkin’s Lymphoma in a Crohn’s Disease Patient Treated with Azathioprine and Infliximab - Elmijbri, Fatma F.; El-Magbri, Mariam; Hermiz, Joshua; Summad, Sahar H.; Magbri, Awad (British Journal of Healthcare and Medical Research, 2024)
Malignancy in patients with inflammatory bowel disease (IBD) is ranked second behind cardiovascular diseases as the leading cause of death. People with IBD are prone to develop a variety of extraintestinal malignancies, particularly lymphomas. Many of these malignancies are non-Hodgkin lymphomas (NHL). Hodgkin lymphoma (HL) is a rather uncommon lymphoproliferative condition to occur in IBD. To date, there have been just a few cases of HL in IBD patients reported in the literature. Modern treatment regimen for Crohn’s disease (CD) has helped prevent enterectomy, intestinal perforation, or stenosis. Thiopurine is a proven maintenance therapy for CD, while tumour necrosis factor (TNF) inhibitors are effective for remission induction and maintenance treatment. Despite the increased likelihood of malignancy associated with treating CD with these agents, the risk is worth the complications. As these patients require long-term treatment to keep the disease at bay. Here we report a case of HL developing in a patient with CD being treated with both azathioprine and infliximab. The occurrence of HL in IBD patients should be considered a complication to therapy, especially if they are subjected to long-term treatment with these agents.